A Swedish national study: Immigrant-country of birth status and child welfare compulsory care among a sample of parents with risky substance use. (March 2020) - He, Amy S.; Padyab, Mojgan; Sedivy, Jennifer A.; Lundgren, Lena
Abstract: Background: Sweden has a high percentage of foreign-born residents (18.5 %) and one of the highest overdose death rates in Europe. For immigrant parents with risky substance use (RSU), risk factors associated with immigration status (e.g., economic strain and psychological stress) potentially heightening the risk of involvement with the child welfare system (CWS). Using Swedish registry national data, this study explored the relationship between immigration-country of birth status, psychosocial risk factors, and child compulsory care for parents with RSU. Methods: Study sample consisted of 5932 parents from 65 Swedish municipalities assessed for psychosocial problems (including alcohol and drug use) using the Addiction Severity Index (2007–2017). Stepwise multinomial logistic regression models examined the relationship between immigration-country of birth status (Swedish born, Nordic-born, and non-Nordic born), psychosocial problems, and compulsory care in the CWS. Results: Compared to Swedish-born parents, parents not born in Sweden, Norway, Denmark or Finland (non-Nordic born parents) had a lower probability of children living in compulsory care (family homes or institutions). However, after accounting for psychosocial problems, immigration status was no longer significantly associated with children's living arrangements. Conclusions: Study findings indicate that parental immigrant status (even among parents dealing with RSU) in itself is not a risk factor for compulsory care in the CWS. Moreover, parental employment and health problems posed greater risk for children being in compulsory care. Receipt of targeted services for employment and health problems may help to maintain stable child living arrangements for immigrant parents dealing with RSU.